Route of exposure alters inflammation and lung function responses to diesel exhaust - Larcombe, A.; Phan, J.; Kicic, A.; Perks, K.; Mead-Hunter, Ryan; Mullins, Ben (Informa Healthcare, 2014)
Context: Mice are commonly used in studies investigating the effects of diesel exhaust exposure on respiratory health. A plethora of studies in this field has resulted in a range of exposure protocols, from inhalation of diesel exhaust, to the administration (via various routes) of diesel exhaust particles in solution. Objective: In this study, we compared the physiological consequences of short-term exposure to diesel exhaust via inhalation to those due to exposure to the same diesel exhaust particles suspended in solution and delivered intranasally. Materials and methods: Adult BALB/c mice were exposed to diesel exhaust via inhalation for 2hours per day for 8 days. A representative, simultaneous sample of particles was collected and a second group of mice then exposed to them suspended in saline. A low and a high-dose were studied, with these matched based on respiratory parameters. Six and twenty-four hours after the last exposure we measured bronchoalveolar inflammation, lung volume, lung function and the amount of elemental carbon in alveolar macrophages. Results: Exposure via either route elicited pulmonary inflammation and changes in lung function. We identified significant differences in response between the two routes of exposure, with mice exposed via inhalation generally displaying more realistic dose-response relationships. Mice exposed via intranasal instillation responded more variably, with little influence of dose. Conclusions: Our results suggest that selection of the route of exposure is of critical importance in studies such as this. Further, inhalation exposure, while more methodologically difficult, resulted in responses more akin to those seen in humans.